2018
DOI: 10.3389/fimmu.2018.00954
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-Class I Alleles and the Autoreactive T Cell Response in Psoriasis Pathogenesis

Abstract: Psoriasis is a complex immune-mediated inflammatory skin disease characterized by T-cell-driven epidermal hyperplasia. It occurs on a strong genetic predisposition. The human leukocyte antigen (HLA)-class I allele HLA-C*06:02 on psoriasis susceptibility locus 1 (PSORS1 on 6p21.3) is the main psoriasis risk gene. Other HLA-class I alleles encoding HLA molecules presenting overlapping peptide repertoires show associations with psoriasis as well. Outside the major histocompatibility complex region, genome-wide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 65 publications
5
53
0
4
Order By: Relevance
“…What exactly triggers the inflammation in the skin of psoriasis patients is not clear. One possibility is that T cells recognize an autoantigen in the skin, and after their activation, they secrete key cytokines such as IL-17A, IL-22, and TNFa (Prinz, 2018). These cytokines trigger the local cells, such as the KCs, leading to the production of chemokines that initiate neutrophil infiltrations to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…What exactly triggers the inflammation in the skin of psoriasis patients is not clear. One possibility is that T cells recognize an autoantigen in the skin, and after their activation, they secrete key cytokines such as IL-17A, IL-22, and TNFa (Prinz, 2018). These cytokines trigger the local cells, such as the KCs, leading to the production of chemokines that initiate neutrophil infiltrations to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Early danger signals induce T helper type 17 (or ILC3) differentiation. These cells migrate into skin, recognize autoantigens that are presented by distinct major histocompatibility complex class I molecules (Prinz, 2018), and secrete IL-17A/F, IL-21, and IL-22. Keratinocytes respond to IL-17 homo-or heterodimers via a dimeric receptor that includes IL-17RA (Eyerich et al, 2017).…”
mentioning
confidence: 99%
“…3 Psoriatic patients carrying the HLA-C*06:02 allele have improved response to ustekinumab compared to those without, 4-6 and aside from HLA-C*06:02, psoriasis is associated with HLA-C*12:03, HLA-C*07:01, HLA-C*07:02 and HLA-C*07:04. 7 Here, we have used high-resolution HLA typing to evaluate the role of HLA-C antigen variants on effectiveness and drug survival of ustekinumab in patients with moderate-severe psoriasis over 2 years.…”
mentioning
confidence: 99%
“…6 Further studies have reported that low-dose bexarotene can be effective either as monotherapy or as combination treatment. 2,6,7 The Cutaneous Lymphoma Italian Study Group (CLISG) investigated the efficacy of low-dose bexarotene as adjuvant therapy. 7 Despite its heterogeneous population consisting of MF/SS and peripheral T-cell lymphoma patients, the overall response rate was 75% and median progression-free survival was 25 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation